Pi as Cosmic Fingerprint: A Multidisciplinary Review of a Mathematical Constant in Science, Scripture, and the Argument from Design - Belay Sitotaw Goshu (Britain International of Exact Sciences (BIoEx) Journal, 2026)
The mathematical constant π (approximately 3.14159) appears ubiquitously across geometry, physics, probability, and cosmology. Its universality and non-arbitrariness have prompted philosophical and theological questions about whether π is a human tool, a discovered law, or evidence of design. Purpose: This multidisciplinary review integrates mathematics, physics, astronomy, biblical hermeneutics, theology, and philosophy of science to evaluate the Argument from Design using π. The review synthesizes peer-reviewed literature, scriptural analysis (1 Kings 7:23), and philosophical critiques, including theistic and naturalistic counterarguments. π's universality, logical necessity, and unreasonable effectiveness (Wigner, 1960) are compatible with theism but do not prove it. Major counterarguments include π as human abstraction (Rosen, 2012), logical necessity (Carroll, 2016), no causal connection, God of the gaps (Stenger, 2007), and multiverse hypotheses (Tegmark, 2014). π functions as a "Rorschach test" for worldviews, scientists see a tool, and theologians see a signature. The design argument is probabilistic, not deductive. Future research should integrate empirical studies on mathematical cognition and cross-cultural perceptions of constants.